Pengembangan Media Pop-Up Book Berbasis Budaya Palembang untuk Menanamkan Rasa Cinta Tanah Air di RA Perwanida 2 Palembang - Pety Damayanti; Izza Fitri; Tutut Handayani (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the lack of use of learning media on the topic “I Love Indonesia” ar RA Perwanida 2 Palembang, which has resulted in low focus and interest in learning among studets. In fact, instilling a sense of patriotism from an early age is very important. The purpose of this study is to develop a Palembang culture-based pop-up book media to instill a sense of patriotism in early childhood. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were class B5 students of RA Perwanida 2 Palembang. Data collection techniques included observation, interviews, questionnaires, and documentation, with data analysis conducted through validity, practicality, and effectiveness tests. The validity test results showed that the media was categorized as highly valid: material expert I (74%), material expert II (82.85%), language expert (90%), and media expert (98.57%). The practicality test by practitioners scored 94.54% (very practical). The effectiveness test in the initial field trial showed results of 80% (interview) and 91% (instrument), while in the main field trial the results were 80% (interview) and 92.01% (instrument). The hypothesis test showed that the t-count was 56.55 > t-table 2.04, indicating a significant influence of using the media. Thus, the Palembang culture-based pop-up book media is declared valid, practical, and effective for instilling a sense of patriotism.